FEATURES OF IMMUNE STATUS INDICATORS IN HERPES INFECTION - Akhmedova Dilfuza; Umarova Tamila Abdufattoevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Introduction. The clinical outcome of primary herpes infection (HI) is largely determined by the immune status of the individual. At the same time, it should be noted that the nature of pathogenetic changes in patients with herpes is largely influenced by the ability of the viral genome to integrate into the host cell genome, particularly in paravertebral ganglia, as well as the tropism of HSV and other herpesviruses for blood cells and immune cells (erythrocytes, platelets, granulocytes, macrophages, lymphocytes).